Comparative analysis of the degradation potential of enzymes obtained from Escherichia coli against toxicity of VAT dyes through molecular docking - Muhammad Naveed; Arooj Arshad; Tariq Aziz; Adeeba Ali; Shumaila Ibrahim; Aliyya Atta; Maida Salah Ud Din; Abid Sarwar; Mi-tub Alharbi; Abdullah F. Alasmari (Desalination and Water Treatment, 2025)
The current study assessed the ability of specific enzymes produced by Escherichia coli strains to degrade vat dyes of great environmental concern as pollutants in the textile industry. Vat dyes are highly persistent and significantly contribute to water pollution. The enzymes selected for this study were aryl sulfotransferase, azo-reductase, and alkane sulphonate monooxygenase based on their enzymatic activity. Conformational stability was studied for the enzymes using the Expasy ProtParam tool, confirming stability through an instability index < 40. Seven vat dye pollutants were screened (Vat Brown 1, Vat Yellow 20, Vat Blue 4, Vat Yellow 4, Vat Blue 6, Vat Red 1, and Vat Blue 1) and their molecular docking for interaction with the enzymes was performed using PyRx. Interactions were visualized using Discovery Studio. Aryl sulfotransferase had the greatest binding energy (-13.4 kcal/mol) for Vat Brown 1; these results were followed by those of azo-reductase (-12.8 kcal/mol) and alkane sulphonate monooxygenase (-11.5 kcal/mol). Docked complexes were further analyzed to explain the enzyme-ligand interactions. Furthermore, co-expression analysis of genes encoding these enzymes was done using the STRING web server to confirm degradation potential. This shows a sustainable means of mitigating the adverse environmental effects of vat dye- pollutants through enzymatic degradation, thus providing an ecofriendly approach for industrial waste management.